2006
DOI: 10.1186/1471-2180-6-27
|View full text |Cite
|
Sign up to set email alerts
|

The Escherichia coli BarA-UvrY two-component system is a virulence determinant in the urinary tract

Abstract: BackgroundThe Salmonella enterica BarA-SirA, the Erwinia carotovora ExpS-ExpA, the Vibrio cholerae BarA-VarA and the Pseudomonas spp GacS-GacA all belong to the same orthologous family of two-component systems as the Escherichia coli BarA-UvrY. In the first four species it has been demonstrated that disruption of this two-component system leads to a clear reduction in virulence of the bacteria. Our aim was to determine if the Escherichia coli BarA-UvrY two-component system is connected with virulence using a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…It is also reported that pyelonephritogenic E. coli strains are more cytotoxic to cultured human renal tubular epithelial cells and the cytotoxin hemolysin contributes to this potent virulence as well [44]. A previous study showed that disruption of the BarA-UvrY TCS reduced the fitness of the uvrY mutant in a monkey cystitis model [40]. Similarly, in our assay, mutation in uvrY reduces the cytotoxicity to the cultured human kidney (HK-2 cells) and hemolysin production (Figure 3 & 4, Table 4 & 5).…”
Section: Resultsmentioning
confidence: 99%
“…It is also reported that pyelonephritogenic E. coli strains are more cytotoxic to cultured human renal tubular epithelial cells and the cytotoxin hemolysin contributes to this potent virulence as well [44]. A previous study showed that disruption of the BarA-UvrY TCS reduced the fitness of the uvrY mutant in a monkey cystitis model [40]. Similarly, in our assay, mutation in uvrY reduces the cytotoxicity to the cultured human kidney (HK-2 cells) and hemolysin production (Figure 3 & 4, Table 4 & 5).…”
Section: Resultsmentioning
confidence: 99%
“…As a gluconeogenic medium, amino acids and other small metabolites in LB fuel directly into the Krebs (TCA) cycle [24]. After IPTG induction, more gluconeogenesis takes place in order to generate glucose phosphate for the pentose phosphate pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of the response regulator UvrY results in decreased fitness in both monkey cystitis and murine ascending UTI competition models (Tomenius et al, 2006; Palaniyandi et al, 2012), and decreased invasion of uroepithelial cells (Palaniyandi et al, 2012). Thus, the ability to effectively sense and utilize the mixture of gluconeogenic and glycolytic carbon sources within urine is a key metabolic adaption for UPEC survival.…”
Section: Genetic and Metabolic Responses In Upec Pathogenesismentioning
confidence: 99%